Statistical characterization of ionospheric scintillation using a phase-screen model - Nunes, Fernando (2019)
A fast technique to simulate the effect of equatorial ionospheric scintillation on GNSS signals was proposed by the authors in a previous work. The algorithm uses a single-layer phase-screen model of the ionosphere and the scintillation is expressed by the Huygens-Fresnel (HF) integral which can be determined analytically. Herein, we characterize statistically the amplitude and phase obtained with the HF integral for different values of the scintillation index S4. A phase unwrapper is also developed to determine the phase from the modulo two-pi version provided by the argument of the HF integral.